The Effect of Using Clustering Technique on Students’ Achievement in Writing Descriptive Text - Ratna Sari Dewi (English Teaching and Linguistics Journal (ETLiJ), 2020)
The objective of this research was to find out the significant effect of using clustering technique on students’ achievement in writing descriptive text. Culstering technique used to improve students ability in wirting especially writing descriptive text. This research was conducted at SMP Cerdas Murni Tembung Jl. Beringin Pasar VII no.33 Tembung. The method of this research is quantitative method. The total population of this research was 91 students of the academic year 2019/2020. The researcher just took one class as the sample. The sample consisted of 30 students from VIII-1 class and choosen by using cluster random sampling technique. The writer divided the class into two groups, that are experimental group and non-experimental group. The experimental group was taught by using cluster technique. The data for this research taken from pre-test and post-test of the written test. The experimental group was given pre-test and post-test. After the data has been collected, these were analyzed by using t-test formula. The result of the analysis showed that tobserve (5.215) was higher than ttable (1.701) with the level of significant α = 0.05. The final hypothesis showed that Ho was rejected and Ha was accepted. It means that there was a significant effect of using clustering technique on students’ achievement in writing descriptive text.